The Ontological Status of Cloned Humans: An Analysis of Legal Personality within the Indonesian Legal System - Winston Su; Stefanie Vernica Soetedjo; Natania Kayla Tanujaya; Rieven Yehezkiel Nasari; Janice Arivi Puji; Yuwono Prianto (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the development of cloning technology should contribute to human welfare within an ethical and legal framework that upholds human dignity. However, the current reality demonstrates that the absence of clear regulations regarding human cloning creates a legal vacuum that may reduce cloned individuals to mere biological objects and raise ethical concerns regarding the value of humanity itself. This study aims to examine the ontological status and legal personality of cloned humans from the perspectives of legal philosophy and legal personality theory in order to determine whether cloned humans can be regarded as legal subjects possessing rights and obligations equivalent to those of naturally born humans. Employing a socio-legal research method through conceptual and legal-philosophical approaches, this study explores the nature of cloned human existence and the normative construction of legal personality by referring to the ideas of Kant, Bentham, and Radbruch. The findings reveal that cloned humans, based on their biological and rational characteristics, must be recognized as human beings entitled to legal protection and moral recognition, thereby qualifying as legal subjects. Nevertheless, the absence of specific regulations remains a significant obstacle to achieving legal certainty, highlighting the need for a comprehensive legal framework governing human cloning.